THE RELATIONSHIP BETWEEN FOOD CONSUMPTION PATTERNS AND STUNTING TODDLERS IN HULU SUNGAI UTARA REGENCY - Ahmad Suhaimi; Muhammad Aldy; Yudhi Harianto (CV. Radja Publika, 2023)
This research aims to assess food consumption patterns in families with toddlers and their correlation with stunting among toddlers in Hulu Sungai Utara Regency, South Kalimantan Province. The study uses quantitative descriptive methods, including observation, interviews, note-taking, and 24-hour dietary recalls. It employs the Expected Food Pattern (EFP) approach to evaluate toddler food consumption patterns and Chi-Square analysis to explore links between these patterns and stunting. Food consumption patterns vary due to regional resources and cultural norms. Toddlers' average daily energy intake is 1222.7 kcal per capita, with a final EFP score of 83.5, indicating sufficiency but calling for more diversity. Higher EFP scores represent better dietary diversity and nutritional balance (max 100). Cereal foods contribute the most (43.8% % EAR), followed by oils and fats (12.1%), and animal-based foods (10.6%). Conversely, sugar (1.8%) and oily fruit seeds (4.1%) have the lowest % EAR. Chi-Square analysis reveals a significance level of 0.00 (<0.05), rejecting the null hypothesis (H0). Hence, a connection between Expected Food Pattern (EFP) and stunting in North Hulu Sungai Regency is established.